Corporate Social Responsibility Disclosure and Good Corporate Governance: Financial Performance? - Wulandari, Eva Nuriana; Sarasmitha, Citra (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Purpose: This research aims to analyze the influence of Corporate Social Responsibility disclosure and Good Corporate Governance, measured through managerial ownership, institutional ownership, board of directors, and audit committee, on financial performance measured by Return On Asset. Method: This research collected data from 41 energy companies listed on the Indonesia Stock Exchange during the 2021-2023 period using purposive sampling. The research data was obtained through documentation in the form of annual reports and sustainability reports. Data analysis was conducted using multiple linear regression supported by SPSS version 26. Results: The results of this study indicate that Corporate Social Responsibility, managerial ownership, institutional ownership, and the board of directors have a positive and significant impact on Return on Assets, while the audit committee has a negative and significant impact on Return on Assets. Implications: The audit committee needs to maximize its competence, optimize quality and professionalism to enhance its role. Furthermore, it needs to collaborate with management to provide strategic decisions. Novelty: Contributing to energy companies through the use of a CSR index. Institutional ownership as a proxy for Good Corporate Governance remains under-researched